Respuesta :
Answer:
- c = 23/24
Step-by-step explanation:
- c + 3/8 = 1 1/3
- => c + 3/8 = 4/3
- => c = 4/3 - 3/8
- => c = 32/24 - 9/24
- => c = 23/24
Conclusion:
Therefore, the answer is c = 23/24.
Hoped this helped.
[tex]BrainiacUser1357[/tex]
[tex]\huge \bf༆ Answer ༄[/tex]
Let's solve for c ~
- [tex] \sf{c + \dfrac{3}{8} = 1 \dfrac{1}{3}} [/tex]
- [tex] \sf{c = 1 \dfrac{1}{3}} - \dfrac{3}{8} [/tex]
- [tex] \sf{c = \dfrac{4}{3}} - \dfrac{3}{8} [/tex]
- [tex] \sf{c = \dfrac{32 - 9}{24}} [/tex]
- [tex] \sf{c = \dfrac{23}{24}} [/tex]